2010
DOI: 10.1159/000315491
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Perineural Invasion in 239 Consecutive Patients with Pathologically Organ-Confined Prostate Cancer

Abstract: Objective: The aim of our study was to analyze the role of perineural invasion (PNI) as a predictive parameter of outcome after radical prostatectomy (RRP) in pathologically organ-confined prostate cancer (PCa) and to assess its possible correlation with other well-known prognostic features. Patients and Methods: At our institution between January 2000 and December 2007, we prospectively collected data from 251 consecutive patients with pathologically localized PCa after antegrade RRP. In our analysis 239 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…In our study, we confirmed many but also identified PNI as being of prognostic significance, which has not been reported previously in MBC. Its presence, being double most rates reported in FBC [52,53], may be due to frequent subareolar tumour location which is less frequently seen in women, and comparable to frequent perineural involvement seen in other epithelial tumours such as pancreatic [54] and prostatic [55] adenocarcinoma where the organs have closer proximity to nerve bundles. While mixed prognostic significance of PNI has been seen in FBC studies [53], PNI positive tumours have been shown to be more often associated with positive nodal status and hormonal positivity [53], both of which are more commonly seen in MBC in general, and in our study cohort when compared with FBC.…”
Section: Discussionmentioning
confidence: 91%
“…In our study, we confirmed many but also identified PNI as being of prognostic significance, which has not been reported previously in MBC. Its presence, being double most rates reported in FBC [52,53], may be due to frequent subareolar tumour location which is less frequently seen in women, and comparable to frequent perineural involvement seen in other epithelial tumours such as pancreatic [54] and prostatic [55] adenocarcinoma where the organs have closer proximity to nerve bundles. While mixed prognostic significance of PNI has been seen in FBC studies [53], PNI positive tumours have been shown to be more often associated with positive nodal status and hormonal positivity [53], both of which are more commonly seen in MBC in general, and in our study cohort when compared with FBC.…”
Section: Discussionmentioning
confidence: 91%
“…In prostate cancer (PCa), the prevalence of PNI has been reported by many studies in patients with localized PCa. Yet, its incidence varies among different studies, with a proportion ranging from 23% to 90% in the radical prostatectomy (RP) specimen and 7% to 43% in the biopsy specimen (Harnden et al ., ; Merrilees et al ., ; Masieri et al ., ; Tollefson et al ., ). Although the exact clinical value of PNI remains controversial (Zareba et al ., ; Zhang et al ., ), the presence of PNI is still considered as one of the important mechanisms of PCa cells spreading beyond the prostate (Villers et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…This phenomenon clinically is implicated to play a role in several cancers [15] including breast [16], head and neck [17], pancreatic [18], colon [19], penile [20] and prostate [21][26] amongst others. PNI is observed in over 80% of PCa core biopsy specimens [27] and is associated with multiple adverse pathological factors [19], [28][36] including stage, grade, and preoperative PSA. Most clinicians recognize PNI as the leading cause of prostatic egress and the mechanism through which PCa penetrates the prostatic capsule [37]; and, PCa cells have been observed in the endoneurium [38], [39] totally independent of lymphatic or vascular involvement [38].…”
Section: Introductionmentioning
confidence: 99%